Legal Certainty in Law Number 8 of 2016 Concerning Persons with Disabilities in Industrial Relations - Sudradjat, Mohamad Adya Laksmana; Santiago, Faisal (Journal of Social Research, 2023)
Article 1 point 1 of the Law on Persons with Disabilities explains that Persons with Disabilities are any person who experiences physical, intellectual, mental, and/or sensory limitations for a long time in interacting with the environment may experience obstacles and difficulties to participate fully and effectively with other citizens based on equal rights. Based on the description above, the problem is how is the legal certainty of Law Number 8 of 2016 concerning Persons with Disabilities in Industrial Relations? The research method used is normative juridical and empirical juridical. Legal certainty in Law Number 8 of 2016 concerning Persons with Disabilities in industrial relations based on the results of an interview with Mr. Agung as Director of Human Capital PT. Semen Indonesia Group, it can be concluded that there has never been an industrial relations dispute between employees with disabilities and the Company, and to date, there has never been a layoff from the Company. This is by the legal certainty of Law Number 8 of 2016 concerning Persons with Disabilities which requires efforts to regulate law in legislation made by authorized and authoritative parties so that these rules have a juridical aspect that can guarantee certainty that the law functions as a rule that must be obeyed.